Ontological and Epistemological Transformations of Managerial Knowledge in SMEs in the Age of FinTech - Resna Meliawati; Muhammad Syahrudin (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2026)
This study explores the adoption of Financial Technology (FinTech) and how it affects the foundations of managerial knowledge in Small and Medium Enterprises (SMEs) from an ontological and epistemological perspective. Previous studies in this field have focused on the adoption of FinTech in the SME sector, the outcomes, performance, and financial inclusion; however, the broader implications and philosophy on how digital technologies affect managerial knowing have been neglected. Thus, a systematic literature review (SLR) following the PRISMA 2020 guidelines and management research theory building was conducted. The findings highlight three interconnected themes. SME environments of the past are dominated by practice-based, experiential, and contextual forms of managerial knowledge. Next, the rise of algorithms, machine learning, dashboards, and digital platforms fosters a new epistemology which is data-driven and technologised where knowledge is more and more embedded in technology. Finally, the combined presence of these two logics results in an epistemic tension and a hybridised epistemic structure in which managerial knowing becomes a collaborative process between human reasoning and technology. This study, using this synthesis, formulates an initial proposal of a conceptual framework that reconceptualises FinTech as an epistemic infrastructure, rather than a functional one. This perspective builds on theory by explaining how FinTech impacts managerial cognition, the legitimacy of knowledge, and epistemic power within SMEs. The study concludes with a call for future research that examines the cross-cognitive, philosophical, and ethical implications of digital transformation in the context of small businesses.